Cannibalism in the linear pottery culture : the human remains from Herxheim - Boulestin, Bruno, (Archaeopress archaeology., 2015)
The Herxheim enclosure, located in the German region of Palatinate, is one of the major discoveries of the last two decades regarding the Linear Pottery Culture, and probably one of the most significant in advancing understanding of how this culture ended. The spectacular deposits, mostly composed of human remains, recovered on the occasion of the two excavation campaigns carried out on the site, grabbed people's attention and at the same time raised several questions regarding their interpretation, which had so far mostly hesitated between peculiar funerary practices, war and cannibalism. The authors provide here an extensive study of the human remains found at Herxheim, focusing mainly on those recovered during the 2005-2010 excavation campaign.